"Disbelief and Sadness": First-Year Health Profession Students' Perspectives on Medical Errors. Issue 8 (December 2021) - Davis, Beth P.; Clevenger, Carolyn; Dillard, Rebecca; Moulia, Danielle; Ander, Douglas S.
Abstract : Objectives: The aims of the study were to examine the reactions of first-year health profession students to medical errors and determine whether differences exist between disciplines. Methods: After viewing the Team STEPPS Program's Susan Sheridan video that describes two separate medical errors, students from anesthesia assistant, medical imaging, medicine, nursing, physical therapy, and physician assistant programs provided unstructured open responses reflecting on initial impressions of medical errors depicted in the film. Student responses were assessed via inductive coding techniques and thematic analysis and stratified by discipline. Frequencies of key themes were calculated. Descriptive analyses characterized respondents and χ 2 tests compared responses between disciplines. Results: In a review of 373 student responses (80% response rate), 255 students expressed an emotion-based reply, of which 93.75 were negative with such comments as they felt horrified, appalled, and disappointed by the patient's experience. Of the 227 students who commented on blame or fault, 70% felt that a system error was at fault, 45% felt that it was the provider and only 1.3% stated that it was the patient's fault. Of the students who mentioned the context or situation, just more than half felt that the episode was preventable and there was a causal relationship between clinic workers' actions and the medical error. Finally, a high percentage of students had a solutions-oriented response, noting the importance of teamwork and communication in the avoidance of medical errors. Conclusions: First-year health profession students responded to medical error with strong emotion and distress. Their responses largely represent an individualistic view of healthcare in both the causes and solutions to medical errors. No differences in response themes were observed by discipline. This study represents our students' emotional responses to a medical error scenario. The qualitative responses and reactions of students to the Sheridan video offered opportunities to tease out nuances that would otherwise be unavailable in a typical attitudes survey. We noted a individualistic view of healthcare in both the causes and solutions to medical errors. We view these results as an opportunity for interprofessional education in systems-level approaches to improve patient safety. Curricular efforts in interprofessional education, collaborative practice, and patient safety should be driven by these results.